PKM Sosialisasi Dampak Gadget, Bahaya Penyalahgunaan Narkoba dan Pergaulan Bebas - Lensoni Lensoni; Meri Lidiawati; Noeroel Arham; Erna Savitri; Cut Rahmawati (LPPM Universitas Bina Sarana Informatika, 2019)
The development of technology has made changes in human lifestyles which is increasingly complex where everything must be done quickly. One of the sophisticated and flexible technology is a gadget. Gadgets as the dynamic mobile human have a big influence on the lifestyle of modern society. Moreover, sophisticated technology has had a big impact on teenagers. The world of adolescents is very vulnerable to the adverse influence of technology where all things can easily be found by teenagers in gadgets. The most adverse influences of gadgets on teenagers are drugs and promiscuity. With the presence of gadgets, the friendship access opens widely and the access of pornographic content is obtained easily. Based on the eagerness to save the nation's generation, therefore the Community Service was carried out in the adolescents. Moreover, the target of Community Service was the adolescents who are aged 12 to 14 years at Abulyatama Junior High School. The aim of the Community Service was to increase the knowledge of students of Abulyatama Junior High School through the educational knowledge about the impact of using gadgets, the dangers of drug abuse and promiscuity. The activities were carried out by giving lectures and discussions. The approach was done by finding students' problems and giving solutions. The student problems were obtained during the discussion, then the problem solving was presented at the end of the activity. The results of the activity showed that the students had understood the dangers of gadgets for their character building. In addition, they were eager to inform the results of activities to the other friends outside of their school. As the educational institution that is very close to their environment, Abulyatama University is expected to continue to give guidance and support for the adolescents’ activities.